The three musketeers - Dumas, Alexandre, 1802-1870.; Coward, David (New York : Oxford University Press, 1998)
The heroic young d'Artagnan a his noble compatriots Athos, Porthos, and Aramis are pitted against the master of intrigue, Cardinal Richelieu, and the quintessential wicked woman, Lady de Winter.
Translation of: Les trois mousquetaires.
Includes bibliographical references.
Adult
Keywords: Swordplay -- Fiction; Swordplay -- Fiction; France -- History -- Louis XIII, 1610-1643 -- Fiction; France -- History -- 1589-1789, Bourbons -- Fiction